The Use of Dialogue Reading and Role - Playing to Enhance Students’ Speaking Skills - Aqilla, Nofi Arum; As'ad, Fitriah; Marharini, Swasti (Universitas Pahlawan Tuanku Tambusai, 2025)
Teachers may use different ways to encourage students using target language. They may believe the more students practice the language the better their speaking skill will be. This study aims to investigate the use of reading dialogue and role-playing methods in facilitating students’ speaking skills. The study used a qualitative descriptive design by observing the classrooms. The participants were 30 students from Class VIII-B at one of the public junior high schools in Surabaya. The results showed that reading dialogues help students facilitate students’ speaking skills. Through role-playing and dialog reading, students could practice their fluency, accuracy, intonation, non-verbal communication, and confidence. Students became more fluent through repeated performance, more accurate through imitation of modelled sentences, and more expressive through attention to body language and eye contact. Overall, the study suggests that dialogue reading and role-play are effective in facilitating speaking skills, although teachers need to ensure that the activities maximise language exposure rather than focusing solely on creating an enjoyable atmosphere.